Europe's India words, people, empires, 1500-1800 - Subrahmanyam, Sanjay 1961- (Harvard University Press, 2017)
Introduction: Before and beyond "orientalism" -- On the Indo-Portuguese moment -- The question of "Indian religion" -- Of co-production: the case of James Fraser, 1730-50 -- The transition to colonial knowledge -- By way of conclusion: India's Europe